The Ecology of Return: Trauma, Atmosphere, and the Poetics of Water - Samarathunga, Wasantha (Journal of Ecohumanism, 2026)
This article examines the poetic book The Water That Remembers as a model of ecological trauma. The text contains no human speaker and no personal narrative. Instead, it presents a cycle of still water, ripple, sound, mist, rain, reflection and return. These movements form a mandala that mirrors the rhythms of rupture and recurrence described in trauma studies. Drawing on environmental humanities, posthuman memory theory and ecological phenomenology, the article argues that trauma can be understood as a disturbance in the field between self and world. Water, atmosphere and light become sites where memory settles and reappears. The analysis shows how ecological forms can model dissociation, intrusion, repetition and recognition. This approach expands trauma studies beyond the human subject and highlights the role of matter in holding traces of experience. The article proposes an ecological mode of remembering that is relational, cyclical and grounded in the poetics of water.